2015
DOI: 10.1111/soc4.12297
|View full text |Cite
|
Sign up to set email alerts
|

Normative Accountability: How the Medical Model Influences Transgender Identities and Experiences

Abstract: The medicalization of gender variance is a key force in transgender people's experiences of embodiment, identity, and community. While most directly dictating experiences of diagnosis and medical classification, it is important to acknowledge that the effects of medicalization are widespread across social contexts and institutions. I explore the medical model of transgender identity, with special attention to its current diagnostic classification, in order to highlight how transgender people's interactional ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 35 publications
3
88
1
2
Order By: Relevance
“…I was treated as a dependent who needed parents' permission even though children are able to access transition services without parents' permission here because it's a private matter. I could not even start on a low dose because I wasn't planning to change my legal gender, though I had transitioned socially.In each of these examples, we see the same patterns of cisnormativity noted by transmen and transwomen in prior literature (for reviews, see Johnson , ) also finds voice as a foreclosure of fluid possibilities in the lives of fluid people.…”
Section: Foreclosing Fluiditysupporting
confidence: 72%
See 1 more Smart Citation
“…I was treated as a dependent who needed parents' permission even though children are able to access transition services without parents' permission here because it's a private matter. I could not even start on a low dose because I wasn't planning to change my legal gender, though I had transitioned socially.In each of these examples, we see the same patterns of cisnormativity noted by transmen and transwomen in prior literature (for reviews, see Johnson , ) also finds voice as a foreclosure of fluid possibilities in the lives of fluid people.…”
Section: Foreclosing Fluiditysupporting
confidence: 72%
“…In each of these examples, we see the same patterns of cisnormativity noted by transmen and transwomen in prior literature (for reviews, see Johnson 2015Johnson , 2019 also finds voice as a foreclosure of fluid possibilities in the lives of fluid people.…”
Section: Another Genderqueer Pansexual Wrotesupporting
confidence: 71%
“…Yet, members also made clear the importance of medical intervention for many trans people. Given the dominance of the medical frame in social, medical and legal contexts (Johnson ), participants tended to invoke the medical frame strategically in order to facilitate social understanding and medical intervention. Coral, mentioned above, recalled being strategic in her use of a medical frame to secure access to gender affirming care:
When I was going through therapy I had to kind of, I don't want to say act through it, but I felt like I knew what I had to do to get a letter to go to the endocrinologist to get my hormones […] I sat down and they started asking me these questions and I had to be really careful how I said things and what I said because I was like, in the back of my mind, I'm like, this person writes that letter and gets me what I need.
…”
Section: Methodsmentioning
confidence: 99%
“…In a parallel, Serano (2007), a transwoman and biologist, provides a scathing critique of sociologists' emphasis on gender as socially constructed, when many transgender people experience gender as internal and intrinsic. In the same vein, a qualitative study found that transgender people appreciate medicalization, because it validates activism (being transgender is not a "choice") and facilitates gender-affirming medical services (Johnson, 2015(Johnson, , 2019). Yet transgender people also report discomfort at the pathologization of inclusion in the DSM, even with the update from "gender identity disorder" to "gender dysphoria" with the DSM-5 (Johnson, 2019).…”
Section: Pride Identity and Activismmentioning
confidence: 99%
“…In another example, gender is assigned and perceived inconsistently, and non-binary genders occur in other cultures (Barnartt, 2013;Serano, 2007). Yet, in the US, people whose experienced gender does not align with their perceived sex are explicitly framed as disabled through inclusion in the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders (DSM) (Johnson, 2015). In these ways, gender categories were and continue to be explicitly managed through disability ideology.…”
Section: Disability and Gendermentioning
confidence: 99%